Measuring Satisfaction with Pharmacy Education Quality: A Systematic Review of Instruments - Thi Thu Trang, Tran; Thi Song Ha, Nguyen; Thi Thanh Thao, Phan (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2025)
Abstract: Background: Satisfaction with the quality of education is a crucial factor in enhancing training effectiveness to meet stakeholders' expectations. Objective: This study aims to synthesize and evaluate instruments used to measure satisfaction with the quality of pharmacy education, focusing on their structure, reliability, and validity. Methods: The study adhered to PRISMA guidelines, conducting searches in Scopus, PubMed, and ERIC databases up to July 2024, supplemented by a manual search of full-text articles not indexed in these databases. Inclusion criteria covered studies employing instruments to assess satisfaction in pharmacy education. Study quality was evaluated using the Joanna Briggs Institute Checklist for Analytical Cross-Sectional Studies. Results: Nine eligible studies were included in the analysis. The evaluation instruments comprised 4 to 8 key factors, with the most common being facilities, curriculum content, teaching staff, and administrative management. Cronbach’s alpha values ranged from 0.532 to 0.93, indicating varied reliability across instruments. Student satisfaction levels differed by country and were influenced by factors such as infrastructure, teaching methods, and institutional support. Conclusion: This review provides an overview of instruments measuring satisfaction with the quality of pharmacy education. The findings can serve as a foundation for improving pharmacy education programs, emphasizing the balance between theory and practice, upgrading facilities, and enhancing academic support services. Keywords: Satisfaction, pharmacy education quality, instruments.